REGISTRATION OF VOTERS WITHIN THE PERSPECTIVE OF CONSTITUTIONAL DEMOCRACY: CASE STUDY OF REGISTER OF VOTERS IN 2014 GENERAL ELECTION - Zainal Arifin Hoesein (Yustisia, 2016)
ABSTRACT Voting right is citizen’s constitutional rights. There is nothing that can obscure it, not to mention negate it, as long as it is not against the moral, religious, public stability and security values. The action to negate the voting rights is an act of dismissal of democratic constitutional values. Indeed, the democratic values strongly upheld the citizens’ rights, including the voting rights. The correlation between the voting rights and the general election administration is a synergic correlation to create conducive election as mandated by the constitution. Administration role should not have been an obstacle for upholding the constitutional democratic values, rather, it becomes a filter in regulating each citizen in using their voting rights to ensure the legal certainty, either from technical aspects, which is the accurate ballot counting, or from substantive aspect that is to ensure the legal certainty in conducting the accountable general election. In deciding the voters, several things should be prioritized such as first, the administrative management of general election related to the population administration; and, second, the voting rights transformed into the List of Fixed Voters (DPT). Administrative data of population is a baseline data and the data source for establishing the List of Fixed Voters (DPT).